2016
DOI: 10.1002/bmc.3821
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an LC–MS/MS method for the determination of hinokiflavone in rat plasma and its application to a pharmacokinetic study

Abstract: Hinokiflavone has drawn a lot of attention for its multiple biological activities. In this study, a sensitive and selective method for determination of hinokiflavone in rat plasma was developed for the first time, using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Amentoflavone was used as an internal standard. Separation was achieved on a Hypersil Gold C column with isocratic elution using methanol-water (65:35, v/v) as mobile phase at a flow rate of 0.3 mL/min. A triple quadrupole mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…detected the HF content in the plasma of male rats after a single intravenous administration of 1.0 mg/kg HF, and the experiment showed that after administration, HF exhibited biexponential clearance kinetics. The half-life of drug elimination ( t 1/2 ) at the terminal phase was 6.10 ± 1.86 h, which indicated that the stability of free HF was extremely poor (Yin et al., 2017 ). Therefore, the fluorescence intensity of PEG/ZIF-8@HF group is significantly stronger than that of the free HF group, which may be due to the fact that PEG/ZIF-8@HF can completely encapsulate the drug and release it slowly, achieving a better anti-tumor effect than the unstable free HF.…”
Section: Resultsmentioning
confidence: 99%
“…detected the HF content in the plasma of male rats after a single intravenous administration of 1.0 mg/kg HF, and the experiment showed that after administration, HF exhibited biexponential clearance kinetics. The half-life of drug elimination ( t 1/2 ) at the terminal phase was 6.10 ± 1.86 h, which indicated that the stability of free HF was extremely poor (Yin et al., 2017 ). Therefore, the fluorescence intensity of PEG/ZIF-8@HF group is significantly stronger than that of the free HF group, which may be due to the fact that PEG/ZIF-8@HF can completely encapsulate the drug and release it slowly, achieving a better anti-tumor effect than the unstable free HF.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the pharmacokinetics of total hinokiflavone in rat plasma was studied by LC-MS/MS. It was discovered that T 1/2 was 6.10 ± 1.86 h [ 321 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Thus, the natural product is largely metabolized but, nevertheless, the elimination of the natural product is not excessively rapid. A pharmacokinetic study in rat indicated that the half-life of HNK elimination ( t 1/2 ) was 6.1 h and the area under the plasma concentration–time curve value (AUC 0-∞ ) was about 2500 h × ng/mL [ 116 ].…”
Section: Stability Metabolism and Formulation Of Hnkmentioning
confidence: 99%